AplikasiI Klonosewandono Sebagai Bahan Ajar BIPA Pada Ketrampilan Membaca Tingkat Dasar - Ida Yeni Rahmawati; Siti Asiyah; Dyah Mustikasari (JURNAL DIMENSI PENDIDIKAN DAN PEMBELAJARAN, 2020)
This study discusses the application of a BIPA teaching, especially in reading skills through an application. The purpose of this study is to explain the teaching materials presented in the Klonosewandono application at basic level BIPA teaching. The research method used is descriptive qualitative. The reference source used here is in the form of the BIPA AI handbook "Sahabatku Indonesia" published by the Language Agency of the Ministry of Education and Culture. The technique for checking the validity of the data in this study uses method triangulation techniques by checking the understanding of lecturers and students on the use of this application. This is that BIPA teaching materials, especially reading skills presented in the Klonosewandono application, are quite helpful in providing a breakthrough in teaching online or remotely. This application of course also still has a weakness, namely that there are no different types of text presented. Hopefully this application can be used as a source of inspiration for further research that is more complete and innovative.